Arsenic Release from Contaminated Soil of Bangladesh in Natural Field Conditions - Azam, M. S.; Shafiquzzaman, M.; Mishima, Iori; Nakajima, Jun (Journal of Scientific Research, 2009)
Leaching experiment was conducted to understand the mechanism of arsenic release from soil in the natural field conditions. Two types of column were run, one with de-ionized water (DW) and another with synthetic Bangladesh groundwater (GW) as influent which simulated rainfall and groundwater conditions, respectively. As the primary mechanism for the arsenic release from soil it was identified that the redox potential (Eh) was major importance. In highly reducing conditions both arsenic and iron release was high. Released mass of arsenic was higher in DW column than GW column. The difference was caused by the presence of calcium and magnesium ion in the synthetic groundwater. Comparing to the acid-alkali sequential extraction it was found that calcium and magnesium prohibited the release of arsenic bound with iron. The effect of calcium and magnesium was clarified in the batch experiment performed in the study. Keyword: Paddy field; Groundwater; Arsenic; Redox potential; pH. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. Â  DOI: 10.3329/jsr.v1i2.1708